Selective Solid-Phase Extraction of Cd(II) by an Ion-Imprinted Polymer from Environmental Samples - Ge, Yunsong; Huang, Zhangjie; Zhu, Zhongbo (Asian Journal of Chemistry, 2012)
A new ion-imprinted polymers material was synthesized by copolymerization of 4-vinyl pyridine as monomer, ethylene glycol dimethacrylate as crosslinking agent and 2,2'-azobisisobutyronitrile as initiator in the presence of cadmium(II)-octyl benzothiazolyl sulfide complex. The ion-imprinted polymers was used as sorbent in a solid-phase extraction column. The effects of sampling volume, elution conditions, sample pH and sample flow rate on the extraction of cadmium ions form environmental samples were studied. The obtained ion-imprinted polymers particles exhibited excellent selectivity for target ion. The distribution ratio (D) values of Cd(II)- ion-imprinted polymers for Cd(II) were greatly larger than that for Cu(II) and Zn(II). The relative selective factor (AR) values of Cd(II)/Cu(II) and Cd(II)/Zn(II) were 246.9 and 238.4. The maximum adsorption capacity was calculated. The detection limit for 250 mL of sample was 0.2 μg L-1 using flame atomic absorption spectrometry. The analytical results for the certified reference samples (GBW08301) were in a good agreement with the certified value. The relative standard deviation for eleven replicate sample of 5.0 μg L-1 level is 3.2 %. The developed method was successfully applied to the determination of trace cadmium in environmental samples with satisfactory results.